UJI AKTIVITAS ANTIINFLAMASI EKSTRAK ETANOL DAUN KAYU MANIS (Cinnamomum burmanni) PADA MENCIT PUTIH JANTAN - Elisma; Rahmila Yuni Astika; Fathnur Sani K (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2022)
Cinnamon (Cinnamomum burmannii) leaves extract contains secondary metabolites such as flavonoids, saponins, tannins, alakloids, steroids/terpenoids and phenols. The aims of this study was to examine the anti-inflammatory activity of the ethanolic extract of cinnamon leaves topically and to determine the best concentration for the treatment of inflammation. This research is an experimental research with a post test only control group design approach. The treatment group was devided into 5 groups where each treatment consisted of 7 test animals The treatments included positive control (hydrocortisone acetate 2.5%), negative control (vaselin flavum), ethanol extract of cinnamon leaves with concentrations of 5%, 10% and 20%. The results showed that the ethanolic extract of cinnamon leaves had an anti-inflammatory effect statistically had a significant difference between the treatment groups (p<0.05). The best concentration is 20% then followed by 10% and 5%.